The Influence of ABRI (Angkatan Bersenjata Republik Indonesia) on Politics in the New Order Period - Acim; Fatimah Alzahra Odie Khoiriah; Nabiel Gymnastiar Nugroho; Nanda Aryani Agustina (Social Impact Journal, 2022)
The presence of the incident on October 17, 1952, which sparked a demonstration demanding the dissolution of parliament made it one of the most historic events to date. There was a division of the army into two, namely, the first camp only wanted to focus on defense while the second camp wanted to be involved in the political field which resulted in many conflicts so AH Nasution was removed from his position. In writing this article, we use the historical-descriptive method, which is a research methodology in history that has the aim of obtaining an overview and describing phenomena that occurred in the past in a systematic and detailed manner.